Determinação da estrutura tridimensional por difração de raios-X da Brazilian Klebisiella Carbapenemase- BKC-1 - Silva, Paola Jacque De Souza Nascimento Da [UNIFESP] (2019)
Background: The emergence and spread of antimicrobial resistance is one of the biggest threats to global health, particularly among the pathogens of medical significance, as the Gram-negative bacilli and members of the family Enterobacteriaceae, also species Klebsiella pneumoniae. The mechanism of resistance of these pathogens is the production of β-lactamases. These enzymes degrade antimicrobial containing a β-lactam ring. Even though well described the process by which the extended spectrum β-lactamase promote catalysis of antimicrobials β-lactam antibiotics, the mode by which the carbapenemases degrade the carbapenems are not yet fully established. Methods: The aim of this study was to study the structure and the mechanisms of action of a new class A carbapenemase of the Ambler classification scheme, BKC-1, identified in clinical specimes of Klebsiella pneumoniae resistant to carbapenems, isolated from two hospitals located in São Paulo, Brazil. In order to achieve the goal proposed we use recombinant enzyme and the gene blaBKC-1 was cloned and expressed in Escherichia coli BL21 (DE3) derived strains grown to 20° for 16 hours. The conditions of extraction and purification of the recombinant enzyme have been optimized. Different osmotic shock protocols for protein extraction of periplasmic space were realized, the protein fraction of the periplasmic content was treated with ammonium sulphate solution, 85% saturated, to remove some contaminants and allow the reduction of volume of material. Purification of the recombinant protein was performed by the hydrophobic interaction chromatography, ion-exchange and molecular exclusion. The purified protein was stored in 10 mm Tris pH 8.0 to -20°C. For the tests of crystallization was adopted the sitting drop vapor diffusion technique, single crystals were obtained of the BKC, which were submitted to x-ray diffraction. The mutagenesis by PCR-driven overlap extension was used to evaluate the participation of the most conserved amino acid residues in the catalytic activity and mechanism of action of the enzyme. Were produced and sequenced six mutants. The mutant pET-BKC-1-S92A was expressed following the same protocol for protein extraction and purification for the BKC-WT. Was performed several co-cristalização tests for this mutant complexed with different ligands. The best crystals were selected and diffracted x-ray on Laboratório Nacional de Luz Síncrotron, in Campinas-SP. Results: 3D structure of BKC-1 showed similarity to other β- xxi lactamases of the class A, consisting of two domains. The absence of the Cys238 residue and the insertion of the amino acid residue Tyr in the handle (Ω loop) suggest that a greater degree of flexibility of this protein conformational changes occur allows that can explain the carbapenemase activity. The data sets obtained from recombinant protein cocristalização with mutation in the residue Ser92Ala complexed with benzylpenicillin presented low densities, while for the other complexes, were not observed electronic densities which were characteristics of these substances.